THE MISSILE GUIDANCE ESTIMATION USING EXTENDED KALMAN FILTER-UNKNOWN INPUT-WITHOUT DIRECT FEEDTHROUGH (EKF-UI-WDF) METHOD - Subchan Subchan; Tahiyatul Asfihani (IndoMS, 2013)
This paper consider the estimation of the optimal missile guidance which the objective is to minimize the interception time and the energy expen-diture. The proposed Extended Kalman Filter-Unknown Input-Without Direct Feedthrough (EKF-UI-WDF) approach is to estimate the optimal missile guidance and the target acceleration as unknown input to the missile-target interception model. Unknown input is any type of signals without prior information from agiven state model or a measurement. The computational for the EKF-UI-WDF method and optimal missile guidance show the closest range to the missile-target is smaller than using the EKF. However the Mean Squared Error (MSE) of estimating the optimal missile guidance using EKF method is smaller than using EKF-UI-WDF method.DOI : http://dx.doi.org/10.22342/jims.19.1.124.1-14